Transitioning to Aboriginal community control of primary health care: the process and strategies of one community-controlled health organisation in Queensland - Crystal Jongen; Sandra Campbell; Janya McCalman; Ruth Fagan; Kingsley Pearson; Suzanne Andrews (BMC Family Practice, 2020)
Abstract Background Aboriginal Community Controlled Health Services (ACCHSs) play a critical role in providing culturally appropriate, accessible primary healthcare (PHC) for Aboriginal and Torres Strait Islander peoples in Australia. The success of many ACCHSs has led to increased policy support for their growth and development, including the transition of state government administered PHC services to Aboriginal community control in select communities. However, there is minimal published literature available which evaluates such transitions. This paper reports on an evaluation of one ACCHS (Gurriny Yealamucka Health Service)‘s experience of transitioning local PHC services to community control in Yarrabah, Queensland, with a focus on the processes and strategies which were implemented to achieve successful transition. Methods Data was collected from interviews with key personnel involved in the transition and organisational documents from the evaluation period. Face-to-face or telephone interviews were conducted with 14 key stakeholders, audio-recorded and transcribed with written consent. Historical organisational documents were provided by Gurriny. All interview transcripts and documents were imported into NVIVO, coded and analysed using grounded theory methods. Results Gurriny’s journey of achieving community control of PHC in Yarrabah entailed an almost 30 year process of building and demonstrating organisational capacity. The first stage (1986 to 2004) was focused on establishing and developing a community-controlled health service and the second stage (2005–14) on preparing for the transition. Formal handover occurred in June 2014. Stage one strategies included: addressing community social and emotional wellbeing; consulting the community; collaborating with researchers; and, strategically building services, organisation capacity and stakeholder trust. Stage two strategies were: communicating and engaging with stakeholders; ensuring strong governance; planning and developing the services and workforce; assuring quality; and, financial planning, management and modelling. Conclusion Achieving successful transition to community control of PHC for Gurriny entailed a lengthy process of substantial, ongoing organisational growth and development. Gurriny’s experience provides a framework for both governments and the ACCHS sector to inform future transitions of PHC services to Aboriginal community control.